Utilization of Google Trends in Knowing Public Attention to Diabetes in Indonesia in 2018 - Guruh Dewa Prataba; Aida Devanty Putri; Lalu Moh. Arsal Fadila (Indonesian Journal of Data Science, IoT, Machine Learning and Informatics, 2023)
Diabetes is one of the four non-communicable diseases that are prioritized because of the sufferer’s number and the increasing prevalence rate. The results of the 2018 Basic Health Research shows an iceberg phenomenon where there are far more people living with diabetes who have not been diagnosed than those who live with diabetes and know their condition. The public's desire to find out in advance the disease that may be suffered on Google opens up opportunities of research in public concern about diabetes. This research with descriptive analysis aims to describe the public's attention to diabetes based on Google Trends data. The results show that the development of public attention in 2018 tends to fluctuate with the highest index on World Diabetes Day. Then there are provinces that need attention with high diabetes prevalence values ​​but still have a low volume of diabetes-related searches. Most topics related to diabetes are about the drugs, causes, and symptoms of diabetes. So it is necessary to socialize diabetes literacy, especially in areas with low public attention